Effect of Low-Level Laser Therapy in Treatment of Chemotherapy Induced Oral Mucositis - Rezk Allah, Soheir Shehata; Abd Elshafi, Heba Mohamed; Farid, Reem Jan; Hassan, Mohamed Abd Elrahman; Alsirafy, Samy Ahmed (Journal of Lasers in Medical Sciences, 2019)
Introduction: Oral mucositis (OM) is an unavoidable condition of the oral cavity that accompanies chemotherapy for various malignant cases. Chemotherapy-induced oral Mucositis (COM) is a frequent complication due to mucotoxic drugs and is known to deteriorate the general health significantly, while negatively affecting the quality of life (QOL). Studies have reported that low-level laser therapy (LLLT) promotes the tissue healing. The objective of the present study was to explore the efficacy of gallium-arsenide (GaAs) laser in treating COM and its impact on inflammatory cytokine levels in patients receiving chemotherapy for various malignancies. Methods: A total of 80 patients with COM received LLLT 6 days/week. OM was graded according to the World Health Organization (WHO) grading scale. The outcome parameters were the serum levels of tumor necrosis factor-alpha (TNF-α) and interleukin-6 (IL-6) measured before, during and after administration of LLLT. Results: After LLLT, a significant decrease was found in the mean values of mucositis grade from 2.35 ± 0.695 to 1.13 ± 0.333 after (P < 0.001). A significant reduction in the level of TNF-α was found after LLLT among breast cancer patients (P = 0.0045), but not in head and neck cancer and lymphoma patients. A significant reduction was also found in IL-6 level after treatment among head and neck and breast cancer patients (P = 0.0307 and 0.019, respectively). Conclusion: The use of GaAs LLLT in treating COM in patients with various malignancies is well tolerated by patients, it results in improvement of mucositis, however; mechanism of action does not seem to be completely linked to the change of pro or anti-inflammatory cytokines.